Nutritional quality of dysphagia-oriented products sold on the Italian market - Ascrizzi, Giorgio Innocenzo; Martini, Daniela; Piazza, Laura (Frontiers in Nutrition, 2024)
Introduction Dysphagia is a condition characterized by swallowing difficulties that affects an estimated 8% of the population. Management of dysphagia often requires the use of specially formulated food products that are easier to swallow, while still meeting the nutritional needs of the patient. Despite the growing market for dysphagia-oriented products, there is a compelling need for comprehensive evaluations of their nutritional quality to ensure that they adequately support the health and well-being of this vulnerable population. The aims of this study were: (i) to investigate the nutritional composition of different dysphagia products currently sold in Italy, from several leading healthcare companies, by collecting the nutritional information on their packaging; (ii) to compare their energy, nutrient and salt content per 100 g and serving. Methods A total of 70 items, available in the Italian online market were included in the analysis. Results The data showed a wide difference among the six categories of dysphagia-oriented products. Salt content was found to be very high, with medium (>0.3 g/100 g but <1 g/100 g) and high (≥1 g/100 g) content found in 17 and 51% of products, respectively. Overall, the results show high variability in nutritional composition among dysphagia-oriented products currently on the market. Discussion The high presence of salt in more than half of the products raises a critical issue, as it is not in accordance with WHO guidelines and especially with the clinical situation of the dysphagia patient. This research seeks to provide valuable insights into the adequacy of these products in meeting the dietary requirements of individuals with dysphagia, thereby guiding toward more informed and suitable food choices.